2019
DOI: 10.18203/2394-6040.ijcmph20190583
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on self-medication practices among a selected rural community of Hooghly district, West Bengal

Abstract: Background: Medicines are often used incorrectly; around 50% of all medicines are prescribed, dispensed or sold inappropriately, while 50% of patients fail to take their medicines appropriately (WHO 2002). Self-medication is an important concern worldwide and WHO has laid emphasis on correctly investigating and controlling it. Self-medication practices have dramatically increased in the last few decades, especially in developing countries like India. Therefore, the present study was planned to assess the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…[9] In the present study, majority(65%) perceiving the ailment as minor was the leading cause for practicing self-medication, again this confirms the report from studies done in Bangalore and Hooghly. [10,11] With Vol.12; Issue: 7; July 2022 regard to source of getting information, it was found that 52% were referring to previous prescriptions,24% were consulting a local pharmacist,35% were consulting family and friends and 9% were influenced by electronic and print media .These results were similar to the report from the study done in Meghalaya. [12] With respect to buying medicines, majority (92%) of the respondents were buying medicines from medical shops which was similar to the study done in Erode district.…”
Section: Discussionsupporting
confidence: 77%
“…[9] In the present study, majority(65%) perceiving the ailment as minor was the leading cause for practicing self-medication, again this confirms the report from studies done in Bangalore and Hooghly. [10,11] With Vol.12; Issue: 7; July 2022 regard to source of getting information, it was found that 52% were referring to previous prescriptions,24% were consulting a local pharmacist,35% were consulting family and friends and 9% were influenced by electronic and print media .These results were similar to the report from the study done in Meghalaya. [12] With respect to buying medicines, majority (92%) of the respondents were buying medicines from medical shops which was similar to the study done in Erode district.…”
Section: Discussionsupporting
confidence: 77%